Knowledge co-creation across national boundaries: trends and firms' strategies - Su, Chih-Yi; Lin, Bou-Wen; Chen, Chung-Jen (Knowledge management research & practice, 2016)
This paper examines the role, patterns, and characteristics of knowledge co-creation in a cross-border context and develops a theoretical framework to guide empirical exploration of the value of cross-border knowledge. The empirical results reveal an upward trend in the share of cross-border knowledge and show that cross-border knowledge is of higher quality than within-border knowledge in terms of having more forward and backward citations, more claims, and a shorter technology cycle time. Our study also reveals pronounced differences in knowledge co-creation patterns between the triad regions: Japan, Europe and the United States. Moreover, the analysis of three cases, IBM, Hitachi, and Bayer, demonstrates that instead of focusing on conflicts of interest, such leading firms cooperate with foreign competitors to address technological challenges and opportunities, penetrate foreign markets, defend their positions, and advance technological innovations. Overall, our findings provide new evidence regarding the importance of cross-border knowledge co-creation.